2007
DOI: 10.1111/j.1813-6982.2007.00125.x
|View full text |Cite
|
Sign up to set email alerts
|

DEA APPLIED TO A GAUTENG SAMPLE OF PUBLIC HOSPITALS1

Abstract: The research presented in this paper provides an analysis of the delivery of a few health care services by the public sector in Gauteng, South Africa. The data for the study was especially difficult to collect, suggesting the need for hospital level data information systems, as well as staff who are trained to analyze the information collected. The empirical results from the analysis suggest that services provided by small-scale medical facilities waste fewer resources, while medical centres offering more tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
1
12
1
Order By: Relevance
“…In contrast to the analysis in Kibambe and Koch (2007), the inclusion of additional controls does not have much impact on estimated average efficiency by product 8 . However, the inclusion of those controls, which are significant for total patient inefficiency and new patient inefficiency, does impact the point estimates of returns to scale.…”
Section: Resultscontrasting
confidence: 64%
See 2 more Smart Citations
“…In contrast to the analysis in Kibambe and Koch (2007), the inclusion of additional controls does not have much impact on estimated average efficiency by product 8 . However, the inclusion of those controls, which are significant for total patient inefficiency and new patient inefficiency, does impact the point estimates of returns to scale.…”
Section: Resultscontrasting
confidence: 64%
“…(2000, 2001), Zere et al . (2001) and Kibambe and Koch (2007) have found that healthcare production in the South African public sector is rather inefficient. The results presented above suggest that the healthcare production in the South African private sector is also inefficient, and that surgical production, at least in the private sector, when compared to the previously referenced studies on public sector healthcare production, is generally less efficient than general healthcare production in the public sector 15…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Kibambe and Koch [22] found that services provided by small-scale medical facilities waste fewer resources and are more efficient in terms of costs compared with medical centres that offering more technical services.…”
Section: Resultsmentioning
confidence: 99%
“…Later, Banker et al (1984) introduced a DEA estimator allowing for variable returns to scale (VRS) model. Since then, DEA methodology has been applied in different context calculating technical efficiency of different decision making units (Zere et al, 2001;Kibambe and Koch 2007). Our paper applies DEA input oriented models as the decision maker through different governmental policies can have greater control over the inputs compared with the outputs used (Halkos and Tzeremes, 2010b).…”
Section: Performance Measurementsmentioning
confidence: 99%